If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 11p + -66 = 5p Reorder the terms: -66 + 11p = 5p Solving -66 + 11p = 5p Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '-5p' to each side of the equation. -66 + 11p + -5p = 5p + -5p Combine like terms: 11p + -5p = 6p -66 + 6p = 5p + -5p Combine like terms: 5p + -5p = 0 -66 + 6p = 0 Add '66' to each side of the equation. -66 + 66 + 6p = 0 + 66 Combine like terms: -66 + 66 = 0 0 + 6p = 0 + 66 6p = 0 + 66 Combine like terms: 0 + 66 = 66 6p = 66 Divide each side by '6'. p = 11 Simplifying p = 11
| -(a-15)= | | 100+5p=60+2p | | x-2=2-3x | | 7k-49=22+2k | | (5x+2)(2x-5)=0 | | -(-9-4y)= | | g-1=5-1-9 | | -1(p+6)= | | 36y^2-1=15 | | 3.7q-1.9-3.4q=-0.7q-1.9 | | (1-11j)4= | | 3.7q-1.9q-3.4q=-0.7q-1.9 | | 7(11-n)= | | 0.3q-1.9=-0.7q-1.9 | | 12(4-8p)= | | 7+2(a-3)= -9 | | 17(2b+3)= | | 5m+5=7m-7 | | (6y-3)5= | | 3x^3-13x^2+16=0 | | (2h-4)11= | | 3t^2+4t+1=0 | | 3(2+w)= | | g(-1)=5(-1)-9 | | 4x-6x-4=0 | | 4x(x+2)-x(3+4)=2x+18 | | 7(z-4)= | | 4x^2+21x+22=-4x+4 | | 5(x-2)=8#-3 | | 12x-41+5x+5y= | | Y=Ax-Fx-C | | z^6-z^3-2=0 |